EKSISTENSI PERALIHAN NAFKAH SUAMI TERHADAP ISTERI DISABILITAS SEBAGAI PENGEMIS DI NAGARI TABEK PATAH MENURUT HUKUM ISLAM - Roza Roma Pita; Sri Yunarti; Siska Elasta Putri (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
The purpose of this article discussion is to find out and analyze the implementation of disabled wives in begging, the role of ninik mamak against disabled wives who beg for a living, and analysis of Islamic law on disabled wives who beg for a living. This type of research is a field research in Nagari Tabek Patah. While the data sources consist of secondary data and primary data, primary data is obtained through interviews with disabled wives, husbands, families, ninik mamak, and religious leaders in Nagari Tabek Patah, while secondary data is obtained through books, scientific works and journals. Data analysis techniques in the manner proposed by Miles and Huberman. Based on the results of the study, it was concluded that the wife's begging factor was due to large household needs, unable to work other than begging or begging, because the husband gambled, agricultural land or land to work was small, and also one of the husbands accompanied his wife in begging. beg or beg. A review of Islamic law on a disabled wife who works as a beggar to meet the family needs of a gambling husband. It is not justified in Islam because it is contrary to the letter At-Talaq verse 7 which explains that the obligation of living is imposed on the husband not on the wife and the husband's work is not justified in Islam. Likewise, the wife who works as a beggar and the husband also helps by farming but does not meet the necessities of life is also not allowed in Islam.